Investigating the Relationship between COVID-19 In-hospital Death and Acute Kidney Injury - Haghighi, Ramin; Fereyduny, Nikoo; Oghazian, Mohammad Bagher; Haghighi, Ashkan; Bigdeli, Amir; Sahebkar, Amirhossein (Coronaviruses, 2024)
Introduction: Coronavirus Disease 2019 (COVID-19) can induce multiorgan failure, including acute kidney injury (AKI), which is associated with a poor prognosis. Some of these patients develop proteinuria, hematuria, and elevated serum creatinine, therefore some require hemodialysis. This study aimed to investigate the association between in-hospital death due to COVID-19 and the prevalence of AKI. Methods: In a retrospective study, the available data of patients who died because of COVID-19 from April 1 to September 22, 2020 in a referral hospital was investigated using the case census method. Results: A total of 190 patients who died of COVID-19 were evaluated. Of these, 111 (58.42%) had AKI, with 108 (56.84%) being male. The mean age of the subjects was 66.16±15.43 years old. The mean time from hospital admission to death was about 9 days in all patients. Although not statistically significant, the findings showed that patients who developed AKI died sooner. The most frequent underlying diseases were hypertension [n= 101 (53.16%)] and diabetes [n= 44 (23.16%)]. Moreover, a higher proportion of subjects with AKI as compared to those without AKI were admitted to the intensive care unit (ICU), and had abnormal proteinuria profile (p-value=0.045 and 0.025, respectively). Conclusion: The prevalence of AKI was 58.42% in patients who died from COVID-19 disease. Moreover, abnormal proteinuria and ICU admission were significantly higher in COVID-19 patients with AKI than in those without AKI.
Keywords: COVID-19